Corporate Environmental, Social, and Governance (ESG) and SMEs' Value (a Lesson From Indonesian Public SMEs) - Narotama, Bintang; Achsani, Noer Azam; Santoso, Moch. Hadi (Indonesian Journal of Business and Entrepreneurship, 2023)
Corporate Environmental, Social, and Governance (ESG) has prominently emerged to address sustainability challenges. Despite the positive implications in the extant literature, corporate ESG performance was given less attention by small-medium enterprises (SMEs). Hence, this study aims to investigate corporate ESG performance in Indonesian public SMEs and its influence on firm value. The study was conducted on 17 non-financial SMEs consistently listed on IDX PEFINDO25 from 2016 to 2020. The study found a trend of the annual increase in corporate ESG performance of SMEs and disclosure. The detailed level of performance revealed governance performance was featured, followed by social and environmental performance. The regression analysis showed a significantly positive influence of corporate ESG on firm value. Following these positive influences, we suggest that SME managers amplify corporate ESG as a long-term business growth and value-creation strategy. In addition, investors are advised to consider SMEs with higher ESG performance as part of their investment portfolio. Keywords: corporate ESG, disclosure, firm value, SMEs, sustainability challenges